Photooxygenation of Naphthalene. Issue 11 (6th August 2021) - Fudickar, Werner; Linker, Torsten
Abstract: The photooxygenation of naphthalene to the corresponding endoperoxide (EPO) under various conditions is described. Substantial conversion is only observed at −10 °C and after more than two days, indicating that the [4+2] cycloaddition of singlet oxygen to this acene proceeds much more slowly than corresponding reactions of substituted naphthalenes, a rate constant of k =5.4±0.3 M −1 s −1 was determined by competition kinetics. Another problem is the thermal lability and photochemical cleavage of the naphthalene EPO. We investigated the mechanism of this radical process depending on the light source and sensitizer in comparison to known cyclohexadiene EPO. Thus, bisepoxides and keto epoxides are formed after homolysis of the O−O bond by irradiation with sodium lamps or blue LEDs and subsequent cyclization. This process is accelerated by the sensitizers methylene blue and 9, 10‐dicyanoanthracene, indicating an electron transfer mechanism. Finally, the cleavage of the peroxidic bond is inhibited with red LEDs, and photooxygenation under such conditions affords 20 % EPO. Thus, we could demonstrate that contrary to literature statements singlet oxygen does indeed react with naphthalene. Abstract : The light source makes the difference : The first reaction of naphthalene with singlet oxygen is described, although the corresponding endoperoxide is formed very slowly ( k =5.4±0.3 M −1 s −1 at −10 °C). Photolysis of the O−O bond with visible light or blue LEDs to bisepoxides is problematic, which is accelerated by sensitizers remarkably. The best conditions have been found with red LEDs in the presence of methylene blue, affording the endoperoxide in pure form.